ANALISIS PERFORMA MODEL ORGANIC RANKINE CYCLE (ORC) PADA PT. GEO DIPA ENERGI Ltd. DIENG DENGAN VARIASI MEDIUM KERJA - , ADIATIE SUCININGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Geothermal is one of the promising renewable energy sources which needs a large amount of capital cost, therefore it has to meet the thermo-economy efficiency. Thermo-economy efficiency could be achieved by making use all of the possible potencies that geothermal source has. Brine as the product of separation process of two phase geothermal wells and geothermal wells that have low to moderate temperature are some of the examples of the possible candidate. Those type of wells could be exploited by Organic Rankine Cycle (ORC) power generation. This study is intended to obtain optimum condition of each system with different working fluid and comparing the results to pick out the best performance. The chosen refrigerants are R124, R290, R152a. Comparison will be done by considering system efficiency, their power output, environmentaly friendly properties, and heating area needed for the heat exchanger component. The best performance is delivered by system with refrigerant R124 as working fluid, which generates1657.61 kWpower with 8.99% efficiency. It also needs the least heating area as much as 2640.48 m2on the heat-adding component and 353.51 m2on the heat-rejecting component. Refrigerant R290 is the worst working fluid to be applied on the system because it has the lowest efficiency while refrigerant R152a place second-best but need a lot of superheating process.